Characterizing the fungal and bacterial microflora and concentrations in fitness centres - Ramos, Carla A. (2015)
Fitness centres are special places where conditions for microbiological proliferation should be considered. Moisture due to human perspiration and water condensation as a result of human physical activities are prevalent in this type of buildings. Exposure to microbial contaminants is clinically associated with respiratory disorders and people who work out in polluted environments would be susceptible to contaminants. This work studied the indoor air contamination in three gymnasiums in Lisbon. The sampling was performed at two periods: at the opening (morning) and closing (night) of the three gymnasiums. The airborne bacterial and fungal populations were sampled by impaction directly onto Tryptic Soy Agar (for bacteria) and Malt Extract Agar (for fungi) plates, using a Merck MAS-100 air sampler. Higher bacterial concentrations were found at night as compared to the morning but the same behaviour was not found for fungal concentrations. Gram-negative catalase positive cocci were the dominant bacteria in indoor air samples of the studied gymnasiums. In this study, 21 genera/species of fungal colonies were identified. Chrysosporium sp., Chrysonilia sp., Neoscytalidium hialinum, Sepedonium sp. and Penicillium sp. were the most prevalent species identified in the morning, while Cladosporium sp., Penicillium sp., Chrysosporium sp., Acremonium sp. and Chrysonilia sp. were more prevalent at night. A well-designed sanitation and maintenance program for gymnasiums is needed to ensure healthier space for indoor physical activity.